2001
DOI: 10.1007/s11745-001-0414-9
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for co‐oxidation of β‐carotene with oleic acid

Abstract: Oxidation experiments with β-carotene in a lipid solution were conducted under various conditions of temperature, oxygen composition, and lipid content. The experimental results were compared with those using n-decane reported previously. Under all conditions, the oxidation rate in oleic acid was faster than that in n-decane. A novel kinetic model for the co-oxidation of carotene with a lipid was proposed based on the reaction mechanism, which consisted of the oxidation of carotene, the oxidation of oleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…The authors observed that, when oleic acid was the solvent of the reaction, internal oxygen mass transfer from the atmosphere into the oil had to be taken into account, probably because, in this case, oleic acid also consumed oxygen due to its own oxidation, and thus oxygen transfer was the limiting factor. Internal oxygen transfer was thus included in the proposed kinetic model, which was based on the reaction mechanism consisting of the oxidation of β-carotene (7 reactions), the oxidation of oleic acid (2 reactions), and the cross-reaction of β-carotene with oleic acid (1 reaction), i.e., a total of 10 reactions [62]. In a last study [63], oxidation experiments with β-carotene were also performed in oleic acid solvent but with the addition of α-tocopherol.…”
Section: Effect Of Oxygenmentioning
confidence: 99%
“…The authors observed that, when oleic acid was the solvent of the reaction, internal oxygen mass transfer from the atmosphere into the oil had to be taken into account, probably because, in this case, oleic acid also consumed oxygen due to its own oxidation, and thus oxygen transfer was the limiting factor. Internal oxygen transfer was thus included in the proposed kinetic model, which was based on the reaction mechanism consisting of the oxidation of β-carotene (7 reactions), the oxidation of oleic acid (2 reactions), and the cross-reaction of β-carotene with oleic acid (1 reaction), i.e., a total of 10 reactions [62]. In a last study [63], oxidation experiments with β-carotene were also performed in oleic acid solvent but with the addition of α-tocopherol.…”
Section: Effect Of Oxygenmentioning
confidence: 99%
“…Among them, two studies considered permeation as limiting mass transfer phenomena not taking into account diffusion of oxygen within the food sample of study (modelled by Fick's law): either permeation through the packaging coupled to oxygen consumption by ascorbic acid oxidation in orange juice represented by first order kinetics (Ahrne et al, 1997); or oxygen permeation through whey protein coating coupled to oxygen consumption due to lipid oxidation of peanuts described by an apparent zero/first order kinetics (Mate and Krochta, 1998). Two other studies dealt with oxygen diffusion within food (modelled by Fick's law) coupled to b-carotene oxidation in oleic acid, with a kinetic model developed using 10 elementary reactions (Takahashi et al, 2001) or 25 elementary reactions in presence of a-tocopherol (Shibasaki-Kitakawa et al, 2004). Finally, three studies integrated oxygen permeation through packaging, diffusion through food and oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Like the previous studies (3-6), the constants are expressed using the pre-exponential factor, B i , and the activation energy, E i , as These constants, B i and E i , were estimated by fitting Equations 27 and 42 with five sets of the experimental results for the β-carotene oxidation in oleic acid solvent with addition of α-tocopherol. The fitting procedure was the same as that reported previously (3)(4)(5)(6). The experimental and fitted results are shown in Figure 2 by the symbols and the solid lines, respectively.…”
Section: Application Of the Kinetic Modelmentioning
confidence: 91%
“…In this study, a kinetic model describing β-carotene oxidation in oleic acid solvent with addition of α-tocopherol was proposed by combining the previous two models (3,4). Validity of the proposed kinetic model was verified by comparing the experimental and calculated results.…”
mentioning
confidence: 96%
See 1 more Smart Citation